PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS ICT PADA SUBTEMA BERSYUKUR ATAS KEBERAGAMAN UNTUK SISWA KELAS IV SEKOLAH DASAR - Lina Novita; Tustiyana Windiyani; Rifa Fazriani (Universitas Pakuan, 2019)
DEVELOPMENT OF LEARNING MEDIA OF ICT BASED ON SUBTEMA BE GRATEFUL FOR DIVERSITY FOR CLASS IV STUDENTS ELEMENTARY SCHOOL This research is uses development procedures that produce the final product design in the form of developing ICT-based learning media using interactive PowerPoint. This product was developed by researchers combining research steps from Borg and Gall and the ASSURE model. The product developed in this research is ICT-based learning media referring to the 2013 curriculum for fourth grade students of elementary schools. Based on the steps of the development procedure above the researcher only limited to the 5 steps of the development procedure, namely (1) potential and problems, (2) data collection, (3) product design, (4) expert validation, and (5) design revision. This is because the limited time needed in research and ICT-based learning media is made to be a teacher's grip so it is sufficiently validated by four fourth grade elementary school teachers who make ICT-based learning media in the implementation of the 2013 Curriculum aided by researchers